Research progress in the diagnostic methods of lateral lymph node metastasis in low rectal cancer - Zhou Zijian; Zhu Xiaoming; Zhang Wei (结直肠肛门外科)
Lateral lymph node metastasis is one of the main causes of local recurrence after low rectal cancer surgery. The diagnosis of lateral lymph node metastasis in low rectal cancer provides strong evidence for surgeons to perform lateral lymph node dissection. Currently, it mainly relies on preoperative MRI, CT and other imaging methods. In recent years, the intraoperative diagnosis technology for lateral lymph node metastasis in low rectal cancer has been continuously developed. Nano carbon tracer technology, indocyanine green fluorescence imaging, lymphoscintigraphy, and laparoscopic ultrasound have emerged, which are expected to improve the efficiency of diagnosis and guide the operation more effectively. This review provides an overview of the research progress in the diagnostic methods for lateral lymph node metastasis in low rectal cancer.